Exploring the Neural Correlates of Visuospatial Memory: A Comprehensive Review of Brain Activity Assessment in Immersive Virtual Reality Research During the Last Decade - Tania Llana; David Perpetuini; Candela Zorzo; Marta Mendez (Applied Sciences)
Visuospatial memory plays a crucial role in everyday functioning. However, its assessment was less explored compared to other memory systems. Immersive virtual reality (iVR) devices can add valuable information about visuospatial memory providing more realistic and ecological environments and allowing for the recording of brain activity in real time. This present systematic review summarizes the current knowledge of brain dynamics during the execution of iVR-based visuospatial memory tasks. Nine articles were reviewed, employing visuospatial working memory, visuospatial memory recognition, and spatial memory tasks through commercial iVR devices such as HTC Vive or Oculus. Most studies measured brain activity using electroencephalography. The findings highlight different key aspects, such as the sensitivity of the prefrontal cortex under stressful conditions, the relationship between memory load and brain activity, the involvement of medial temporal lobe regions on spatial memory and its improvement using memory reactivation paradigms, the importance of some environmental characteristics (i.e., the space where the task is carried out), and the implication of the parietal cortex in processing allocentric information. These results enhance our understanding of brain activity during iVR-based visuospatial tasks and highlight iVR technologies as promising tools in cognitive neuroscience.